Utility of Multimodal Treatment Protocols in the Management of Scalp Cutaneous Angiosarcoma - Adel Alharbi, MD; Young-Chul Kim, MD; Feras AlShomer, MD, MSc; Jong-Woo Choi, MD, PhD, MMM (Plastic and Reconstructive Surgery, Global Open, 2023)
Background:. Cutaneous angiosarcomas are rare, aggressive tumors with high recurrence and poor prognosis. We share our experiences with the challenging surgical management of these lesions, focusing on both ablative and reconstructive outcomes. Methods:. Retrospective cross-sectional chart review was conducted of patients diagnosed with scalp cutaneous angiosarcoma between 2005 and 2021. Resectability, defect reconstruction, and survival outcomes were analyzed. Results:. Thirty patients were included, 27 (90%) men and three (10%) women, with a mean age at diagnosis of 71.77 ± 7.3 years, and mean follow-up of 429.43 ± 305.6 days. Only 12 patients completed their regular follow-up, while the remaining patients died. There was a median survival of 443.50 days (range, 42–1283) and median time to recurrence of 21 days (range, 30–1690). Multimodal therapy compared with surgery alone had a significantly better overall median survival (468 days versus 71 days; P = 0.021). Defect coverage was obtained in 24 cases (75%) through an anterolateral thigh flap, two patients (6%) with a local transposition flap, and one patient (3%) with a transverse rectus abdominis myocutaneous flap. The remaining three patients received a skin graft. All of the flaps survived, with one requiring a vein graft for venous congestion. Conclusions:. Timely multimodal therapy with a histologically safe margin, combined with adjuvant therapy, improves survival and delays recurrence and metastasis, in cutaneous angiosarcoma patients. An anterolateral thigh flap facilitates the coverage of wide defects. Further investigations of advanced treatment modalities such as immunotherapy and/or gene therapy are required to deal with this highly aggressive tumor.